2021
DOI: 10.3390/cancers13184668
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Relapse Is Associated with Increased NFκB Pathway Activity and Upregulation of the Pro-Survival BCL-2 Protein BFL-1

Abstract: Multiple myeloma (MM) is a hematological malignancy that is still considered incurable due to the development of therapy resistance and subsequent relapse of disease. MM plasma cells (PC) use NFκB signaling to stimulate cell growth and disease progression, and for protection against therapy-induced apoptosis. Amongst its diverse array of target genes, NFκB regulates the expression of pro-survival BCL-2 proteins BCL-XL, BFL-1, and BCL-2. A possible role for BFL-1 in MM is controversial, since BFL-1, encoded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, BCL2A1 is overexpressed in a variety of cancer cells (Vogler 2012). In a recent study, it is reported that disease relapse in MM is related to increased NFκB pathway activity, which causes increased BCL2A1 expression (Spaan et al 2021). Considering the upregulated BCL2A1 expression in young MM patients, it can be hypothesized that BCL2A1 may be a target for treatment with the current anti-cancer drug obatoklax mesylate currently used in acute myeloid leukemia and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, BCL2A1 is overexpressed in a variety of cancer cells (Vogler 2012). In a recent study, it is reported that disease relapse in MM is related to increased NFκB pathway activity, which causes increased BCL2A1 expression (Spaan et al 2021). Considering the upregulated BCL2A1 expression in young MM patients, it can be hypothesized that BCL2A1 may be a target for treatment with the current anti-cancer drug obatoklax mesylate currently used in acute myeloid leukemia and lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…From a gene transcript expression analysis of eight primary multiple myeloma patient samples that relapsed after chemotherapy, BCL2A1 was identified as the most frequently increased factor, suggesting its therapy resistant role in multiple myeloma [ 60 ].…”
Section: Bfl-1 In Drug Resistancementioning
confidence: 99%
“…Functional profiling of BCL2 dependence can also predict clinical response in MM, as an alternative approach to precision medicine that utilizes preclinical BH3 profiling and ex vivo testing with venetoclax to determine what level of ex vivo drug sensitivity is associated with clinical response ( 115 ). Furthermore, disease relapse after treatment resulted in increased NFkB activity and increased BCL2A1 (coding for BFL-1) as well as Bcl-2 and Bcl-xL ( 128 ).…”
Section: Venetoclax Sensitivity In MMmentioning
confidence: 99%